2017
DOI: 10.1016/j.wocn.2017.01.002
|View full text |Cite
|
Sign up to set email alerts
|

Prosodic boundary cues in German: Evidence from the production and perception of bracketed lists

Abstract: International audienceThis study investigates prosodic phrasing of bracketed lists in German. We analyze variation in pauses,phrase-final lengthening and f0 in speech production and how these cues affect boundary perception. In linewith the literature, it was found that pauses are often used to signal intonation phrase boundaries, while finallengthening and f0 are employed across different levels of the prosodic hierarchy. Deviations fromexpectations based on the standard syntax-prosody mapping are interpreted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
30
1
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 36 publications
(42 citation statements)
references
References 57 publications
7
30
1
1
Order By: Relevance
“…Besides numerous linguistic studies that investigated the relationship between pause and boundary perception (e.g., [11,12]), the electrophysiological study by Männel and Friederici [13] revealed that 3-year-olds perceive the boundary also when the existence of a pause is the only acoustic cue marking the boundary. This is in line with the findings of Petrone et al [14], showing that adult German listeners give categorical responses for prosodic boundaries in the case of pauses, while more gradual transitions were observed with f0 and final lengthening cues. Their experimental design, however, did not allow to show the weights of these three cues.…”
Section: Perception Of Prosodic Boundariessupporting
confidence: 93%
“…Besides numerous linguistic studies that investigated the relationship between pause and boundary perception (e.g., [11,12]), the electrophysiological study by Männel and Friederici [13] revealed that 3-year-olds perceive the boundary also when the existence of a pause is the only acoustic cue marking the boundary. This is in line with the findings of Petrone et al [14], showing that adult German listeners give categorical responses for prosodic boundaries in the case of pauses, while more gradual transitions were observed with f0 and final lengthening cues. Their experimental design, however, did not allow to show the weights of these three cues.…”
Section: Perception Of Prosodic Boundariessupporting
confidence: 93%
“…For our manipulation of constituent structure, we used coordinated names (following Lehiste, 1973;van den Berg et al, 1992;Wagner, 2005;Féry and Kentner, 2010;Kentner and Féry, 2013;Petrone et al, 2017). The intended syntac-tic constituent structure was indicated by the placement of commas.…”
Section: Speech Materialsmentioning
confidence: 99%
“…In intonation languages, pitch movements have post-lexical functions indicating prosodic (and syntactic) phrasing and pragmatic functions, such that infants growing up with a non-tone language are not fully naïve to pitch variations. In German, rising pitch contours with a nuclear pitch accent (L * H) are related to sentence internal boundaries of prosodic phrases and to Yes-No Questions (Grice and Baumann, 2002 ; Gussenhoven, 2004 ; Petrone et al, 2017 ). Since questions are frequently used in communication with infants and toddlers to catch their attention (Spinelli et al, 2017 ), and even infants and toddlers show discrimination of question over declarative intonation contours (Geffen and Mintz, 2011 ; Soderstrom et al, 2011 ), our finding that German toddlers discriminate high-rising from mid-level tones at 18 months of age lines up with findings from other studies that assume that the native language intonation system has an impact on lexical tone perception in speakers of non-tone languages.…”
Section: Understanding Developmental Trajectories For Tone Discriminamentioning
confidence: 99%